2021
DOI: 10.9734/jammr/2021/v33i2431241
|View full text |Cite
|
Sign up to set email alerts
|

Health Workers and Users’ Perspective of Quality of Maternal Health Care in Health Facilities in Somali Region of Ethiopia: A Qualitative Study

Abstract: Aims: In spite of   progress made in reducing maternal mortality, there remains a high burden of deaths related to the quality of care mothers receive in low- and middle-income countries. Ethiopia health sector transformation plan focused on improving equity and quality of health care at all levels of the system. The study explored health workers and users’ perspectives of quality of maternal health care in health facilities in Somali Region. Study Design: This was a descriptive study. Place and Du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…A study done in the region on the quality of care reported that most of the health workers expressed their frustration in being able to provide the needed quality of care because their skills and competencies are limited in view of limited access to regular inservice training, supervision and management support by the regional and woreda authorities. 17 The finding on the supportive management as incentive for retention is similar to findings in many studies among various cadres of health workers that report strong leadership and supportive management as important non-financial incentives. [18][19][20] A study in Ghana among health workers in a district hospital reported that among the 4 factor model of non-financial incentives, leadership skill and supervision was ranked first predictor of motivation and retention.…”
Section: Supportive Managementsupporting
confidence: 85%
See 1 more Smart Citation
“…A study done in the region on the quality of care reported that most of the health workers expressed their frustration in being able to provide the needed quality of care because their skills and competencies are limited in view of limited access to regular inservice training, supervision and management support by the regional and woreda authorities. 17 The finding on the supportive management as incentive for retention is similar to findings in many studies among various cadres of health workers that report strong leadership and supportive management as important non-financial incentives. [18][19][20] A study in Ghana among health workers in a district hospital reported that among the 4 factor model of non-financial incentives, leadership skill and supervision was ranked first predictor of motivation and retention.…”
Section: Supportive Managementsupporting
confidence: 85%
“…A study done in the region on the quality of care reported that most of the health workers expressed their frustration in being able to provide the needed quality of care because their skills and competencies are limited in view of limited access to regular in-service training, supervision and management support by the regional and woreda authorities. 17 …”
Section: Discussionmentioning
confidence: 99%